2018
DOI: 10.1002/qre.2297
|View full text |Cite
|
Sign up to set email alerts
|

VSSI median control chart with estimated parameters and measurement errors

Abstract: An adaptive control chart called Shewhart X chart with variable sample size and sampling interval (VSSI) is quicker than Shewhart X chart, X chart with variable sample size (VSS), and X chart with variable sampling interval (VSI) in detecting the mean shifts of a normal process. In practice, the effects of measurement errors on control charts should be included. In this study, we present an VSSI median control chart with estimated parameters in the presence of measurement errors for a normal process. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…where e q T ¼ 1; 0; 0 ð Þis a vector representing the initial probabilities of the modified Markov chain. From Equations (18) and (20), ASS 1 (δ) can be computed as 25…”
Section: Tarl Tsdrl Ass and P(i)mentioning
confidence: 99%
See 1 more Smart Citation
“…where e q T ¼ 1; 0; 0 ð Þis a vector representing the initial probabilities of the modified Markov chain. From Equations (18) and (20), ASS 1 (δ) can be computed as 25…”
Section: Tarl Tsdrl Ass and P(i)mentioning
confidence: 99%
“…Additionally, Yeong et al presented the VSS chart that monitors the CV directly instead of the transformed statistics employed by Castagliola et al Amiri et al extended the VSS approach to the exponentially weighted moving average (EWMA) control chart. More research works on the VSS control charts can be found in Mahadik, Wu and Luo, Noorossana and Maryam, Mahadik, Cheng and Wang, Aslam et al, Zhou and Lian, Nyau et al, and Lee . In VSS charts, the sample sizes change as a function of the prior sample position, ie, small or large sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the presence of measurement errors significantly affect the performance of the monitoring procedure. Cheng and Wang [20] presented a VSSI median control chart with estimated parameters in the presence of measurement errors. Their results showed that the VSSI median chart performs better than the Shewhart median, VSS median and VSI median control charts in terms of the average time to signal.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal VSSI X chart was also proposed by using the estimated parameters [21] and adjusted loss function [22]. Reference [23] introduced the VSSI median control chart with estimated parameters and measurement errors while reference [24] studied the effect of measurement errors on the performance of the VSSI X chart. References [25] and [26] considered the VSSI chart for the process mean using auxiliary information and the coefficient of variation, respectively.…”
Section: Introductionmentioning
confidence: 99%